When the sacred organizes space in Timimoun (Algeria) - Djeradi, Mustapha Ameur (Technium Social Sciences Journal, 2022)
This paper attempts to show the hold of the sacred on the urban reality of Timimoun. This human settlement, where the permanence of the sacred is found in the structuring and management of space, is a disputed space. To illustrate this, using a hybrid historical-inductive method, a very significant case study has been chosen. It concerns a housing estate, where the mrabtin of the zawiya of Sidi -l- Haj Belqasam challenge the construction of housing close to the hufra: official reason invoked the Sbu', a sacred element. Timimoun is a disputed space, even today, the traces of these confrontations persist in the social structuring and spatial configurations.